Positive Effect of Teriparatide on Areal Bone Mineral Density in Young Women with Anorexia Nervosa: A Pilot Study - Milos, Gabriella (Calcif Tissue Int, 2021)
The present pilot study investigated the effect of Teriparatide 1–34 rh-PTH (TPT) in young women diagnosed with anorexia nervosa (AN), and markedly compromised Bone Mineral Density (BMD). Patients were included who had (i) very low BMD (defined as Z-Score <  − 2.5 or T-Score <  − 2.5 if available) in at least one of the assessed localizations (lumbar spine L1–L4, total hip, femoral neck) without any previous fragility fracture; or (ii) low bone mineral density (defined as Z-Score <  − 1.5 or T-Score <  − 1.5 if available) in at least one of the assessed localizations (lumbar spine L1–L4, total hip, femoral neck) and at least one previous fragility fracture. Ten patients with an age range of 21–33 were recruited and their bone outcome was assessed after 12, 18, and 24 months. After 24 months of TPT treatment, BMD improved by 13.5% in the spine, 5.0% in the femoral neck, and 4.0% in the hip. Radius cortical bone density (− 2.6%) and radius cortical thickness (− 6.4%) decreased significantly, while in tibia there was no significant decrease. Neither in radius nor in tibia a significant change in trabecular bone parameters occurred. During the treatment, the patients’ body weight did not increase significantly. Patients did not experience severe adverse events; only mild side effects were observed. Although these results emerged from a single-arm prospective study, it seems that AN patients with a severely compromised bone situation can benefit from TPT. Larger studies are needed to ascertain the effect of this promising substance.